Enhanced As (V) Adsorption Properties in Sn-Substituted Goethites - Changes in Chemical Reactivity and Surface Characteristics - Larralde, Ana Laura (International Journal of Innovative Research in Engineering & Management, 2015)
In this work, the adsorption of arsenic (V) onto crystalline substituted goethites was studied for samples with different Sn- contents. The highest Sn-content of the prepared samples was 5.5 (expressed as 100?[Sn]/[Sn]+[Fe]) as all attempts to prepare goethites with higher tin content only rendered amorphous materials. The Sn-for-Fe substitution caused changes on the physico-chemical properties of the obtained samples, and the thermal analysis indicated that the formed Sn-goethites were metal-deficient goethites with increased thermal stabilization towards decomposition to hematite. BET surface analysis evidenced the presence of large mesoporous or macroporous in all samples and the following trend in SSA values: GSn5.5 (54.90±0.08) > GSn0 (25.75±0.09) > GSn2.1 (17.19±0.05 m2g-1). The As(V) adsorption presented a maximum at pH = 5.50 ± 0.05 for all samples and the data showed that GSn5.5 nearly duplicates the amount of As adsorbed per gram of pure goethite. To evaluate the chemical stability of the samples, dissolution kinetics measurements in acidic conditions were also performed. Dissolution rate followed the trend GSn2.1 > GSn0 > GSn5.5. The facts that GSn5.5 dissolves slower than the pure sample and that adsorbs twice as much as pure goethite indicate that GSn5.5 is a promising agent for As(V) removal technologies.